A Solvent‐dependent Fluorogenic Probe Containing Julolidine for Cr(III) and Cu(II). (23rd May 2016) - Anjong, Tikum Florence; Park, Yu Mi; Jang, Ha Yoon; Kim, Jinheung
Abstract : A julolidine‐containing naphthylamine probe (EW1) was prepared for sensing specific metal ions. Probe EW1 afforded a broad low fluorescence at 500–600 nm in acetonitrile, but gave a relatively stronger fluorescence at 540 nm in methanol. EW1 showed a selective turn‐on emission for Cr 3+ in CH3 CN. Upon treatment with Cr 3+, a strong emission was observed at 515 nm, but other metal ions, such as K +, Ag +, Ca 2+, Zn 2+, Co 2+, Ni 2+, Cu 2+, Cd 2+, Hg 2+, Fe 2+, and Fe 3+, failed to induce such an emission band. A clean isosbestic point appeared at 405 nm in the UV–vis titration with Cr 3+ . The emission intensity of EW1 was enhanced with incremental addition of Cr 3+, indicating the formation of a 1:1 complex of the probe EW1 and chromium ion. However, EW1 showed a selective turn‐off response with Cu 2+ in CH3 OH. The emission band of EW1 at 540 nm was quenched only with Cu 2+ and not with other control metal ions. The absorption band of EW1 at 410 nm progressively decreased, and a new absorption at 390 nm appeared upon progressive addition of Cu 2+ . All spectroscopic titration experiments and ESI mass data provided evidence for the formation of a 1:1 complex between EW1 and Cu 2+ . Abstract :